Bioatividade do extrato do endófito Diaporthe infecunda LGMF694 para controle de Sclerotinia sclerotiorum e Colletotrichum truncatum - Tortelli, Brenda (2022)
Colletotrichum truncatum and Sclerotinia sclerotiorum are fungal pathogens that can be spread by soybean seeds, usually controlled by seed treatment with fungicides. However, due to the increase in fungicide-resistant isolates and the harmful effects of pesticides on the environment and human health, the search for alternative methods of controlling common pathogens by seeds is underway. Thus, this study evaluated whether the extract of Diaporthe infecunda, an endophyte from the leaves of Schinus terebinthifolius, inhibits the growth of C. truncatum and S. sclerotiorum, and improves the sanitary quality of soybean seeds when artificially inoculated with these etiological agents. For this, the in vitro diffusion tests in a isolate were perfected and, later, the germination tests were carried out, tests of minimum maturation and concentrates, colder propagation in seeds, concentrates, more innocuous through water propagation in restricted seeds. With the same seeds, the germination test was carried out in sand and then the fresh length of the plant was measured, mass and dry mass. It can be seen that the extractor of Diaporthe infertile inhibited the in vitro growth of C. truncatum in 94.4% and 83.8% of S. sclerotiorum in vitro. It also decreases the disease of pathogens in the seeds, however, it decreases the germinative power. The Diaporthe infecunda extract LGMF694 controls the pathogens, however, it reduces the germinative power of the seeds. Therefore, formulations from new application methods must be applied with the objective of minimizing the effect observed in this study.